2020
DOI: 10.1007/s11469-020-00448-0
|View full text |Cite
|
Sign up to set email alerts
|

The Fear of COVID-19 Scale: Psychometric Properties of the Ethiopian Amharic Version

Abstract: Fear is an adaptive response that alerts individuals to the presence of a danger or threat. However, in the context of the current novel coronavirus disease 2019 (COVID-19) pandemic, the fear experienced could be intense because the number of victims of the virus is continuously increasing globally and is inducing severe mental health concerns. The seven-item Fear of COVID-19 Scale (FCV-19S) assesses the severity of fear related to COVID-19 and has already been validated in many languages. The present study ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
60
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 42 publications
7
60
2
Order By: Relevance
“…The unidimensionality was consistent with several other studies, 10,11,[13][14][15]18,20,23,24,29,30 including three conducted with the Brazilian Portuguese-speaking population 33,35,36 and one African study conducted with the Ethiopian Amharic-speaking population. 31 In the present study, Mozambicans had an overall average fear score of 20.5 (SD = 5.8), which was lower than that reported in the Ethiopian study (21.65, SD = 5.58, for those living in the country, and 20.79, SD = 5.78, for those not living in the country). Additionally, 49.1% of the Mozambicans showed a level of fear greater than 20.5.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…The unidimensionality was consistent with several other studies, 10,11,[13][14][15]18,20,23,24,29,30 including three conducted with the Brazilian Portuguese-speaking population 33,35,36 and one African study conducted with the Ethiopian Amharic-speaking population. 31 In the present study, Mozambicans had an overall average fear score of 20.5 (SD = 5.8), which was lower than that reported in the Ethiopian study (21.65, SD = 5.58, for those living in the country, and 20.79, SD = 5.78, for those not living in the country). Additionally, 49.1% of the Mozambicans showed a level of fear greater than 20.5.…”
Section: Discussioncontrasting
confidence: 84%
“…Since the publication of the Persian version of the FCV-19S, 8 it has been translated into several other languages and evaluated based on samples from various countries: English [United Kingdom, New Zealand, USA, and India], [9][10][11][12] [24][25][26][27] Japanese [Japan], 28 Greek [Greece], 29 Vietnamese [Vietnam], 30 Ethiopian Amharic [Ethiopia], 31 and Portuguese [Brazil]. [32][33][34][35][36] The psychometric properties of the FCV-19S in these languages proved to be robust, with internal consistency reliability supported by Cronbach's alpha greater than 0.80.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these restrictive measures aimed to ensure social distancing and help to decrease the rate of COVID-19 infection, such limitations imposed a burden on the mental health of the general population that is now emerging, with reports of increased levels of stress, depression, anxiety, insomnia, feelings of loneliness, cases of post-traumatic stress and suicide [ 3 7 ]. In a study with the Portuguese population 25% of the adults reported moderate to severe symptoms of anxiety, depression and post-traumatic stress due to lockdown [ 8 ] and a recent study showed that higher levels of intolerance for uncertainty seemed to have a direct impact on mental wellbeing during the COVID-19 pandemic, with rumination and fear of COVID-19 mediating this association [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Ahorsu et al (2020) recently developed the Fear of , to briefly assess the fear of COVID-19. The FCV-19S was translated into different languages and has been shown to have adequate psychometric evidence of validity and reliability (Alyami et al, 2020;Andrade et al, 2020;Bitan et al, 2020;Broche-P erez et al, 2020;Caycho-Rodr ıguez et al, 2020Elemo et al, 2020;Giordani et al, 2020;Haktanir et al, 2020;Huarcaya-Victoria et al, 2020;Mahmood et al, 2020;Mart ınez-Lorca et al, 2020;Masuyama et al, 2020;Pang et al, 2020;Perz et al, 2020;Reznik et al, 2020;Sakib et al, 2020;Soraci et al, 2020;St anculescu, 2021;Tsipropoulou et al, 2020;Wakashima et al, 2020). However, many of these investigations have concluded that the FCV-19S has a one factor structure, while others report the presence of two factors related to physiological and emotional responses to the fear of COVID-19 (Bitan et al, 2020;Caycho-Rodr ıguez et al, 2020Huarcaya-Victoria et al, 2020;Masuyama et al, 2020;Reznik et al, 2020).…”
mentioning
confidence: 99%